The effect of tell me more (TMM) usability on students’ segmental and suprasegmental pronunciation - Uthayakumaran, Arulselvi (2019)
The use of English as the common official language is recognized in over 50 countries. While the classrooms are constantly flooded with materials of teaching and learning to support elements like reading, writing, speaking and listening in English, one aspect has remained perplexing for the learners of English; pronunciation. The teaching of pronunciation had drastically improved from when it was first introduced. Amidst the increased use of technology to learn pronunciation in Malaysia, the use of language learning software to learn pronunciation has yet to gain popularity. A preliminary study was conducted to identify the general concerns surrounding the use of TMM to learn pronunciation. The preliminary study found that 56% of the students were not comfortable to be corrected on pronunciation errors through a language learning software. In order to further examine student’s inhibition on receiving pronunciation correction from TMM, this study investigates students’ apprehensions on usability through the use of a language learning software like Tell Me More (TMM) on students segmental and suprasegmental pronunciation. First, a questionnaire was distributed to find out how students perceived the usability of the built-in pronunciation modules in TMM to learn segmental and suprasegmental pronunciation. Then, in the second part of the study, an interview was conducted to investigate the user experience of students on TMM. The findings from the questionnaire attested that 187 students found the built-in pronunciation modules in TMM attributed to positively in improving the students segmental and suprasegmental pronunciation. However the findings from the interview demonstrated varying user experiences while using TMM. By documenting the effect of TMM built-in pronunciation modules and its user experience, this research hopes to highlight how well a language learning software like Tell Me More achieves pronunciation goals with engineering undergraduates in Malaysia and how students feel while interacting with digital products like TMM.